Pelatihan Pengolahan Sumber Daya Hasil Laut Kepada Kelompok Pemberdayaan Usaha dan Potensi (KPUP) Desa Sungai Kakap - William Wendy Ary; Fitri Yutika; Fry Melda Saragih (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM), Univesitas Kristen Indonesia, 2023)
Abstract Blue economy has become a leading sector in Indonesia and contributes greatly to the Indonesian economy through the productivity of marine products and employment. Sungai Kakap Village is one of the villages famous for its marine product potential in West Kalimantan Province. However, problems related to processing marine products into high-value alternative processed products are the main problems that hinder the optimization of marine products in this village. The aims of this service activity are to find solutions to these problems and build partnerships with the KPUP Sungai Kakap Village. The method used in this community service is Participatory Rural Appraisal (PRA) and is carried out in stages, namely 1) Identification and Analysis, 2) Assistance Planning, 3) Implementation of Assistance, 4) Monitoring and Evaluation, and 5) Final Report. The results of this community service are the majority of participants who attended felt very satisfied and felt high benefits from this service activity, especially in the aspects of delivering material and providing technology. However, aspects of the solution can be improved Keywords: Blue Economy; Empowerment; Fishery; Potency; Kakap River